Nghiên cứu ảnh hưởng của cao su lỏng CTBN đến tính chất cơ học của màng phủ polyme trên cơ sở nhựa epoxy DER 671x75 và DER 331 đóng rắn bằng Epicure 3125 - Diệu, Trần Vĩnh; Huy Cường, Huỳnh Lê; Thành, Nguyễn Đắc (Vietnam Journal of Chemistry, 2015)
Study on the effects of rubber liquid CTBN (copolymer carboxyl terminated butadien-acrylonitrile) to mechanical properties of polymer coating film based on epoxy resins DER 331 and DER 671X75. Dispersion of CTBN in epoxy resin by stirring 500 rpm at 60-65 oC in 30 minute. The results show that CTBN is good dispersed in epoxy DER 331 and 10 % CTBN in DER 331 has increased mechanical properties of polymer coating film epoxy DER 331. However, CTBN is bad dispersed in epoxy DER 671X75 and decreases mechanical properties of polymer film epoxy DER 671X75.